THE DEVELOPMENT OF GERMAN LANGUANGE INSTRUCTIONAL MATERIAL BASED ON COMIC TO IMPROVE VOCABULARY AND SPEAKING SKILL - Rati Mayasari; Johanes Sapri; Turdjai Turdjai (DIADIK, 2018)
The purpose of this research was to develop the german language instructional material for the second semester class X SMAN 2 Bengkulu that can improve student’s speaking skills and vocabulary. This method used is Research and Development, which refers to  the development model of Borg and Gall with 6 stages, namely (1) Research and Information Collecting, (2) Planning, (3) Develop Preliminary of Product, (4) Preliminary Field Testing, and (5) Main Product Revision, (6) Main Field Testing. This research and development produce a instructional material based on comic  were validate by expert judgment. Effectiveness test shows that comic based instructional material applied in the experimental class can improve student’s vocabulary and speaking skill.